2022
DOI: 10.36740/wlek20220420120
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches to Diagnosis and Treatment of Hirschsprung Disease in Newborns and Infants (Literature Review and First-Hand Experience)

Abstract: The aim: To analyze the current state of the issue of Hirschsprung disease in newborns and infants on the basis of literature data and first-hand experience. Conclusions: 1. Hirschsprung disease should be suspected in all newborns with late meconium passage. 2. The main methods of diagnosing Hirschsprung disease in newborns and infants are the assessment of anamnestic data, clinical manifestations and features of the clinical course of the pathology, contrast enema, morphological examination of rectal biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Calretinin IHC was applied to all 36 studied cases, and 27 (75%) of the cases were identified as HD, while the remaining 9 (25%) cases were identified as non-HD Table (2) The IHC for Calretinin was applied to all 36 cases after the application of Calretinin IHC; out of 36 cases, 27 (75%) cases were confirmed as HD while the remaining 9 (25%) cases were confirmed as non-HD; hence, all suspicious HD cases had been confirmed and categorized in HD and non-HD. In our study, strong calretinin immunoreactivity was observed in all ganglionic segments (non-HD cases), figure (4), showing positive expression between the two muscularis layers and positive expression in the submucosa layer. Whereas any immunoreactivity was not observed in almost all aganglionic segments (HD cases), (Figure 5) shows a negative expression of Calretinin in the two layers of the muscularis layer while showing a complete absence of staining expression of Calretinin in the mucosa and submucosa layers.…”
Section: Immunohistochemistry Of Calretininsupporting
confidence: 59%
See 2 more Smart Citations
“…Calretinin IHC was applied to all 36 studied cases, and 27 (75%) of the cases were identified as HD, while the remaining 9 (25%) cases were identified as non-HD Table (2) The IHC for Calretinin was applied to all 36 cases after the application of Calretinin IHC; out of 36 cases, 27 (75%) cases were confirmed as HD while the remaining 9 (25%) cases were confirmed as non-HD; hence, all suspicious HD cases had been confirmed and categorized in HD and non-HD. In our study, strong calretinin immunoreactivity was observed in all ganglionic segments (non-HD cases), figure (4), showing positive expression between the two muscularis layers and positive expression in the submucosa layer. Whereas any immunoreactivity was not observed in almost all aganglionic segments (HD cases), (Figure 5) shows a negative expression of Calretinin in the two layers of the muscularis layer while showing a complete absence of staining expression of Calretinin in the mucosa and submucosa layers.…”
Section: Immunohistochemistry Of Calretininsupporting
confidence: 59%
“…In a recent study, some worrying maternal risk factors were highlighted during pregnancy were the age of the mother at conception, shown in Table (4), maternal illness, intake of drugs, type of Childbirth, and number of previous maternal abortions, all of them offer a non-significant difference (p>0.05) between the HD group and non-HD group. Still, consanguineous marriage was detected and showed a significant difference (p<0.05) between the HD group and non-HD group shown in table (5).…”
Section: Prenatal Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous cytoplasmic cells, an eccentric circular nucleus, a noticeable nucleolus, a perinuclear pallor, and peripheral chromatin are examples of classic cytological characteristics. Ganglion cells are typically, but not always, clustered in ganglia and/or in contact with the neuropil (neurites and glia) [33].…”
Section: Histopathological Studymentioning
confidence: 99%
“…HD is categorized into short-segment HD when the aganglionic segment is confined to the rectum and sigmoid colon. On the other hand, long-segment HD extends beyond the sigmoid colon and encompasses more extensive portions of the colon [ 7 ].…”
Section: Introductionmentioning
confidence: 99%